In vivo assessment of pharmacokinetic interactions of empagliflozin and henagliflozin with sorafenib: an animal-based study - Wenyu Du; Zihan Liu; Zhi Wang; Xin Zhou; Zhanjun Dong; Ying Li (PeerJ, 2025)
Background Sorafenib is a multi-targeted tyrosine kinase inhibitor (TKI) used for the treatment of advanced renal cell carcinoma, hepatocellular carcinoma (HCC), and radioactive iodine-resistant thyroid carcinoma. Notably, glucose transporters sodium-glucose cotransporter 2 (SGLT2) and glucose transporter 1 are highly expressed in HCC and functionally promote tumorigenicity, which increase the possibility of coadministration of TKIs with SGLT2 inhibitors. Therefore, this study aimed to investigate the pharmacokinetic profiles of coadministration of sorafenib with novel SGLT2 inhibitors, either empagliflozin or henagliflozin and to explore their potential mechanisms. Methods Male Sprague-Dawley (SD) rats were divided into seven groups (n = 6) that received: sorafenib (1), empagliflozin and sorafenib (2), henagliflozin and sorafenib (3), empagliflozin (4), sorafenib and empagliflozin (5), henagliflozin (6), sorafenib and henagliflozin (7). Blood samples were collected at multiple time points to measure plasma drug concentrations using UPLC-MS/MS, and pharmacokinetic parameters were calculated. In addition, messenger RNA (mRNA) expression was measured by quantitative polymerase chain reaction (RT-qPCR) to explore underlying mechanisms of interaction. Data analyses were conducted using DAS 2.1.1 software. A P-value of < 0.05 was used as the level of statistical significance. Results The study revealed that sorafenib slightly increased the plasma concentration-time curves (AUC0–t and AUC0–∞) of empagliflozin, whereas the apparent clearance (CLz/F) and apparent volume of distribution (Vz/F) significantly decreased. Similarly, sorafenib increased the AUC0–t, AUC0–∞ and the maximum plasma concentrations (Cmax) of henagliflozin and decreased the CLz/F. Besides, coadministration of empagliflozin decreased the CLz/F, increased the AUC0–∞ and Cmax of sorafenib When coadministered with henagliflozin, the AUC0–t and AUC0–∞ of sorafenib significantly increased by 67% and 80%, respectively, accompanied by decrease in the CLz/F. Furthermore, PCR results demonstrated that sorafenib decreased the expression of Ugt2b7 in intestinal tissue. Empagliflozin and henagliflozin inhibited Oatp1b2 expression in the liver and P-gp expression in the liver and intestines. Conclusions These pharmacokinetic interactions provide valuable insights for future studies on optimizing the dosing regimens of sorafenib in combination with empagliflozin or henagliflozin, potentially reducing toxicity risks and improving the safety of coadministration in clinical settings.